2022
DOI: 10.3390/ph15030290
|View full text |Cite
|
Sign up to set email alerts
|

l-Arginine and Beetroot Extract Supplementation in the Prevention of Sarcopenia

Abstract: Aging is associated with a significant decline in neuromuscular function, leading to a reduction in muscle mass and strength. The aim of the present report was to evaluate the effect of supplementation with nitric oxide precursors (l-arginine and beetroot extract) in muscular function during a training period of 6 weeks in elderly men and women. The study (double-blind, placebo-controlled) involved 66 subjects randomly divided into three groups: placebo, arginine-supplemented and beetroot extract-supplemented.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…The present study showed significant increases in leg LM after 8 weeks of CIT supplementation with the addition of SVLIRT during the last 4 weeks compared to PL. In older obese rats, 12 weeks of ARG supplementation alone enhanced soleus muscle mass via NO production and protein synthesis [ 54 ], but no effect was found in older adults [ 55 ]. On the other hand, findings in malnourished rats and older adults supplemented with CIT alone showed improvements in muscle protein synthesis [ 56 ] and total LM [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study showed significant increases in leg LM after 8 weeks of CIT supplementation with the addition of SVLIRT during the last 4 weeks compared to PL. In older obese rats, 12 weeks of ARG supplementation alone enhanced soleus muscle mass via NO production and protein synthesis [ 54 ], but no effect was found in older adults [ 55 ]. On the other hand, findings in malnourished rats and older adults supplemented with CIT alone showed improvements in muscle protein synthesis [ 56 ] and total LM [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy between the previous and our findings may be attributed to lower CIT dose and duration of the combined intervention. In addition, ARG (3 g/day) supplementation during a combined aerobic and strength training for 6 weeks did not increase LM in older adults [ 55 ]. Low ARG dose and high ARG catabolism by intestinal arginase may have resulted in reduced circulating ARG availability for effectiveness in skeletal muscles.…”
Section: Discussionmentioning
confidence: 99%
“…A total of twelve RCTs involving 500 participants (301 cases and 299 controls) were included in this meta-analysis (14,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) . Six of the studies had two trial arms (14,25,26,28,29,31) .…”
Section: Study Characteristicsmentioning
confidence: 99%
“…A total of twelve RCTs involving 500 participants (301 cases and 299 controls) were included in this meta-analysis (14,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) . Six of the studies had two trial arms (14,25,26,28,29,31) . Table 1 provides the characteristics of the twelve included trials.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation